Pengaruh firm size dan der terhadap roe pada perusahaan asuransi periode 2016 – 2021 - Subagja, Muhamad Syidik; Hasanuh, Nanu; Suartini, Sri; Sulistiyo, Hari; Saputri, Ani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine whether there is an effect of Debt to Equity Ratio (DER) and Firm Size on Return on Equity (ROE) in insurance companies listed on the IDX from 2016 to 2021. This study uses quantitative methods, the population of this study is companies insurance available on the IDX in 2016 to 2021. The technique used to take samples in this study is purposive sampling. The result of this research is that the partial firm size test has no effect on Return on Equity (ROE). In the partial test, Debt to Equity Ratio (DER) has a significant effect on Return on Equity (ROE). In a simultaneous test (simultaneously) Firm Size and Debt to Equity Ratio (DER) both have a significant effect on Return on Equity (ROE).